2x+26=90
Tìm x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2x2−10x−3x−2x2−26=02x2−10x−3x−2x2−26=0
13x−26=0−13x−26=0
x=−2
`2x^2 + 10x + 3x - 2x^2 = 26`
`<=> 13x = 26`
`<=> x = 2`
Ta có: 2x(x – 5) – x(3 + 2x) = 26
⇔ 2 x 2 – 10x – 3x – 2 x 2 =26
⇔ - 13x = 26
⇔ x = - 2
Ta có: 2x(x – 5) – x(3 + 2x) = 26
⇔ 2x2 – 10x – 3x – 2x2 =26
⇔ - 13x = 26
⇔ x = - 2
2x(x-5)-x(3+2x)=26
<=>2x2-10x-3x-2x2=26
<=>-13x =26
<=> x =-2
Vậy x=-2
2x(x-5)+x(3+2x)=26
2x2-10x+3x+2x2=26
4x2-7x=26
x(4x-7)=26
... (tự lập bảng tìm tiếp)
2x(x-5)+x(3+2x) = 26
<=> 2x2 -10x + 3x + 2x2 = 26
<=> 13x = 26
<=> x = 2
\(2x\left(x-5\right)-x\left(3+2x\right)=26\)
\(\Leftrightarrow2x^2-10x-3x-2x^2=26\)
\(\Leftrightarrow-13x=26\)
\(\Leftrightarrow x=-2\)
Bài làm:
Ta có: \(2x\left(x-5\right)-x\left(3+2x\right)=26\)
\(\Leftrightarrow2x^2-10x-3x-2x^2-26=0\)
\(\Leftrightarrow-13x=26\)
\(\Rightarrow x=-2\)
x(2x - 3) - 2(3 - 2x) = 0
x(2x - 3) + 2(2x - 3) = 0
(2x - 3)(x + 2) = 0
\(\left[\begin{array}{nghiempt}2x-3=0\\x+2=0\end{array}\right.\)
\(\left[\begin{array}{nghiempt}x=\frac{3}{2}\\x=-2\end{array}\right.\)
2x(x - 5) - x(3 + 2x) = 26
2x2 - 10x - 3x - 2x2 = 26
- 13x = 26
x = - 26 : 13
x = - 2
2x+26=90
x =(90-26):2
x =32
Ta có :\(2^x+26=90\)
\(\Rightarrow2^x=64\)
\(\Rightarrow2^x=2^8\)
\(\Rightarrow x=8\)
Vậy \(x=8\)